Education for Self-Effacement - A Student's View. (28th August 2022) - Kimari, Wangui
Abstract : Considering the ultimate limitations of instructing Kenya's children in 'civilised' acts like eating a banana with a knife and fork at the expense of an education true to the nation's history, Wangui Kimari wonders whether the current educational system simply upholds students' self-effacement. When my sister was in primary school (the school where we all were had a supposedly pious nature that was the talk of town), like all of the students within this institution she had to take a mandatory 'ethics' class. The title of this class appeared to us ambivalent, big and intimidating, but from what we could garner, 'ethics' were simply tacit rules that we needed to embody in order to live (or pretend to live) in religious harmony with each other.